Sepsis and the Risks of Long-Term Renal Adverse Outcomes in Patients With Chronic Kidney Disease - Ou, Shuo-Ming; Lee, Kuo-Hua; Tsai, Ming-Tsun; Tseng, Wei-Cheng; Chu, Yuan-Chia; Tarng, Der-Cherng (Frontiers in Medicine, 2022)
Background Sepsis is known to cause renal function fluctuations during hospitalization, but whether these patients discharged from sepsis were still at greater risks of long-term renal adverse outcomes remains unknown. Methods From 2011 to 2018, we included 1,12,628 patients with chronic kidney disease (CKD) aged ≥ 20 years. The patients with CKD were further divided into 11,661 sepsis group and 1,00,967 non-sepsis group. The following outcome of interest was included: all-cause mortality, readmission for acute kidney injury, estimated glomerular filtration rate decline ≥50% or doubling of serum creatinine, and end-stage renal disease. Results After propensity score matching, the sepsis group was at higher risks of all-cause mortality [hazard ratio (HR) 1.39, 95% CI, 1.31–1.47], readmission for acute kidney injury (HR 1.67, 95% CI 1.58–1.76), eGFR decline ≥ 50% or doubling of serum creatinine (HR 3.34, 95% CI 2.78–4.01), and end-stage renal disease (HR 1.43, 95% CI 1.34–1.53) than non-sepsis group. Conclusions Our study found that patients with CKD discharged from hospitalization for sepsis have higher risks of subsequent renal adverse events.